Pengaruh Dana Alokasi Umum dan Dana Otonomi Khusus terhadap Belanja Modal Kabupaten Nduga - Ance Marjun; saprudin Saprudin; Novaliastuti Masiaga; Mohamad Abdul Radjak Masjhur; Olfin Ishak; Lianti Polapa (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2026)
This study aims to determine and analyze the simultaneous and partial effects of the General Allocation Fund (DAU) and the Special Autonomy Fund (DOK) on Capital Expenditure in the Nduga Regency Government, Highland Papua Province. The background of this research is based on the phenomenon of obstacles in achieving economic growth in Nduga Regency, both in terms of revenue and expenditure realization, despite being granted broad autonomy and transfer fund support from the central government. The research method used is quantitative with multiple linear regression analysis using budgetary data over a 10-year period. The results indicate that, simultaneously, DAU and DOK have a significant influence on Capital Expenditure with an F-value of 9.493 and a significance level of 0.000. These variables are able to explain 33.9% of the variation in Capital Expenditure. Partially, DAU is proven to have a positive and significant effect on Capital Expenditure. Conversely, DOK does not have a significant effect on Capital Expenditure in Nduga Regency. This is presumably because DOK is primarily allocated to social programs, basic services, and specific financing that are not always directly reflected in physical capital expenditure, as well as constraints in budget planning and absorption within the special autonomy region